“Harsh” sanctions for “budgetary sinners”. An analysis of the debate on the European Fiscal Compact in Austrian opinion-forming quality media - Pühringer, Stefan (Momentum Quarterly, 2015)
This article investigates the discourse on the European Fiscal Compact in Austrian quality newspapers. On the basis of specific clauses of the Fiscal Compact and its implementation process it first demonstrates that the transfer of political power from the legislative to executive authorities can be interpreted as a post-democratic phenomenon although it partially does not even comply with (post) democratic minimum standards. In a second step, six argumentative patterns in favor of the Fiscal Compact in opinion-forming newspapers will be identified by applying a critical discourse-analysis approach. It will be illustrated that political decisions about fiscal-policy measures are discursively transformed in a moral dichotomy of “good” and “bad” economic policy while those who support the “bad moral” are blamed as “sinners” of “debt-making”. At the same time (financial) markets and EU executive authorities are provided with discursive and real political power to punish “moral misconducts” with “severe sanctions”. This kind of moral framing ensures that the economic and political foundations of the debate remain largely ignored.